Parental Roles and Challenges in Managing Pediatric Obesity: Insights from Focus Group Interviews in Korea - Jieun Ju; Jahye Jung; Yong Hee Hong; Minsoo Shin; Yoon Lee; Ah-Ram Sul (Journal of Obesity & Metabolic Syndrome)
Background : Pediatric obesity is a global public health concern. South Korea is witnessing a notable increase in obesity rates among children and adolescents, despite various governmental interventions. Parents play a crucial role in preventing and managing pediatric obesity, as they are typically the primary observers of their child’s weight and daily habits. Methods : This study involved 10 parents of overweight or obese children and adolescents in South Korea, identified from a 2023 Student Health Examination. Focus group interviews were conducted to explore participants’ experiences, followed by a rigorous qualitative content analysis of the data. Results : The analysis revealed one main theme, parental roles and challenges in managing pediatric obesity, that encompassed five categories: parental awareness and perception of pediatric obesity; causes of pediatric obesity; parental strategies for managing obesity; barriers to management; and support systems and resources. Parental recognition of their child’s obesity was predominantly initiated through student health examinations at school, and the cause of obesity was multifactorial. Parents use various strategies, such as dietary changes and exercise promotion, but face barriers, including stigma and resource constraints. Parents demand comprehensive support from schools, healthcare providers, and community programs to effectively manage obesity. Conclusion : These findings highlight the need for tailored interventions to address parents’ specific obstacles in managing pediatric obesity. Enhancing parental awareness, providing clear information, and strengthening support systems are essential for preventing and managing pediatric obesity in South Korea.